Comparison of Oral Health Impact Profile index and Oral Index of Daily Performance as predictors of quality of life of patients with orofacial pain - Kolude, Bamidele; Gbadebo, Shakeerah O. (Journal of Stomatology, 2017)
Introduction. Oral health-related quality of life instruments were developed separately to assess quality of life with added advantage of patient feedback. Aim of the study. To determine the reliability of OHIP and OIDP as predictors of quality of life (QoL) of patients with orofacial pain (OFP). Methods. Survey of QoL of patients at a dental clinic. A 14-item OHIP and 10- item OIDP questionnaires were submitted to patients seen during the study period. The questionnaires also included pain diagnosis and measurement of pain using the Visual Analogue Scale. The data were analyzed using SPSS version 20. Reliability of instruments was tested with Cronbach’s alpha. (P value was at ≤0.05). Results. Two hundred and ninety-five respondents participated. Mean age was 39.8±18.1 years, mean VAS 5.5 ± 2.9, the prevalence, extent and mean severity score of OHIP-14 were 64.7%, 2.8±3.6 and 17.8±12.6, respectively. The OIDP surface count (SC) and OIDP Additive (ADD) were 70.2% and 16.98±21.93, respectively. VAS, OHIP and OIDP showed low, positive but significant correlation. Cronbach’s alpha reliability indices for OHIP and OIDP were 0.93 and 0.94, respectively. Both instruments showed significant impact of OFP on eating, (OHIP p= 0.002, OIDP p=0.003), sleeping (OIDP, p =0.004), and diet (OHIP, p= 0.014). Conclusion. Both instruments showed high reliability and validity indices in assessing impact of FP on the quality of life among affected individuals.